A clinical study on the preservation of pulp sensitivity in affected teeth with jaw cysts using concentrated growth factor: a retrospective Cross-sectional study - Wenjie Zhou; Chuanqing Mao; Ge Shi; Meng Lu; Yongzhen Lai; Chengyong Wang; Yilin Li; Weihui Chen (Scientific Reports)
Abstract Jaw cysts commonly affect the oral and maxillofacial region. This study aimed to evaluate the effect of Concentrated Growth Factor (CGF) application during jaw cyst surgery on postoperative pulp sensitivity changes in affected teeth. This retrospective cross-sectional study included fifty-one patients with jaw cysts, categorized into four groups based on the postoperative filling material used Group A (CGF), Group B (CGF + Bio-Gene), Group C (Bio-Gene) and Group D (Control). Clinical follow-up data, including electric pulp testing results, tooth color changes, gingival healing status, and radiographic evaluations, were collected at 2 weeks and at 3 to 6 months post-surgery. One-way analysis of variance (Kruskal-Wallis test) and linear regression analysis were employed to analyze bone regeneration, changes in pulp sensitivity, and their potential correlations. Results indicated that pulp sensitivity in affected teeth significantly improved at 6 months post-surgery in Group A and Group B compared to pre-surgery levels, with statistically significant differences (p = 0.04; p = 0.043). Conversely, no significant changes in pulp sensitivity were observed in Group C and Group D before and after surgery (p = 0.29; p = 0.867). Additionally, pulp sensitivity recovery was negatively correlated with age but showed no correlation with Hounsfield unit (Hu) values in the apical region or bone formation rates in the cyst cavity. The application of CGF following cyst enucleation aids in restoring blood circulation in affected teeth with sluggish pulp vitality, thereby enhancing the pulp preservation rate and warranting clinical promotion.